The Impact of Islamic-Based Positive Psychology on Decreasing Depressive Symptoms among Beneficiaries at PPSW Wanodyatama - Fachry Muhammad; Rini Lestari (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
High vulnerability to depression is experienced by beneficiaries at the Women's Social Service Center (PPSW) Wanodyatama. The depressive symptoms observed include reluctance to participate in activities, excessive feelings of guilt, pessimistic views about the future, and suicidal ideation. This study aims to examine the effectiveness of Islamic-based positive psychology in reducing depressive symptoms among beneficiaries at PPSW Wanodyatama. A quantitative experimental approach was employed using a one-group pretest–posttest design. The research sample consisted of 10 participants selected using purposive sampling who met the criteria for moderate to severe depression based on screening with the DASS-21 instrument. Depression scores were measured using the Beck Depression Inventory-II (BDI-II) before and after the intervention. The intervention was an Islamic-based positive psychology training program conducted over two days, comprising six sessions. Data were analyzed using the non-parametric Wilcoxon Signed-Rank Test. The results showed no significant difference in depression scores between pretest and posttest (z = -0.204; p = 0.919; p > 0.05). This indicates that, statistically, Islamic-based positive psychology training was not effective in reducing depressive symptoms overall; however, descriptive analysis revealed a reduction in symptoms among some individuals. Factors such as cognitive load, low intrinsic motivation, and an unsupportive institutional environment are suspected to have influenced these results. This study implies that psychological intervention approaches need to be adapted to participants' conditions and environmental contexts to achieve optimal outcomes.